Corporate Controversies and Market-to-Book: The Moderating Role of ESG Practices - Keidann Soschinski, Caroline (2024)
Purpose – The aim of this study is to analyze the moderating role of ESG practices in the relationship between corporate controversies and companies’ market-tobook performance. Theoretical framework – ESG effect, ESG controversies and market performance. Design/methodology/approach – We investigated 3,267 companies from 20 countries with the highest GDP in 2021. ESG ratings and other variables were collected from the Refinitiv database. The cross-country analysis considered panel data regressions with fixed effects by year, industry and country from 2016 to 2020. Findings – The results showed that corporate controversies have a negative effect on companies’ market performance, while engagement in ESG practices has a positive effect. However, when analyzing the relationship between corporate controversies and market-to-book value in companies with high ESG ratings, the negative effect of controversies is not significant. Practical & social implications of research – This research contributes by indicating the negative consequences of corporate controversies in terms of market performance and signaling that ESG practices are important to meet the needsof stakeholders, but are not enough to mitigate the impact of ESG controversies on market performance. Originality/value – To the best of our knowledge, this is the first paper to demonstrate that ESG practices are not strong enough to mitigate the negative effects of ESG controversies on market performance in a large sample. Keywords: Corporate controversies, ESG, market-to-book.